Unprecedented recent summer warmth in Arctic Canada - Miller, Gifford; Lehman, S.; Refsnider, K.; Southon, J.; Zhong, Y. (American Geophysical Union, 2013)
Arctic air temperatures have increased in recent decades, along with documented reductions in sea ice, glacier size, and snow cover. However, the extent to which recent Arctic warming has been anomalous with respect to long-term natural climate variability remains uncertain. Here we use 145 radiocarbon dates on rooted tundra plants revealed by receding cold-based ice caps in the eastern Canadian Arctic to show that 5000years of regional summertime cooling has been reversed, with average summer temperatures of the last similar to 100years now higher than during any century in more than 44,000years, including the peak warmth of the early Holocene when high-latitude summer insolation was 9% greater than present. Reconstructed changes in snowline elevation suggest that summers cooled similar to 2.7 degrees C over the past 5000years, approximately twice the response predicted by Coupled Model Intercomparison Project Phase 5 climate models. Our results indicate that anthropogenic increases in greenhouse gases have led to unprecedented regional warmth.